Physician Electronic Health Record Usage as Affected by the COVID-19 Pandemic - Ruan, Elise; Beiser, Moshe; Lu, Vivian; Paul, Soaptarshi; Ni, Jason; Nazar, Nijas; Liu, Jianyou; Kim, Mimi; Epstein, Eric; Keller, Marla; Kitsis, Elizabeth; Tomer, Yaron; Jariwala, Sunit P. (Applied Clinical Informatics, 2022)
Objectives To utilize metrics from physician action logs to analyze volume, physician efficiency and burden as impacted by telemedicine implementation during the COVID-19 (coronavirus disease 2019) pandemic, and physician characteristics such as gender, years since graduation, and specialty category.Methods We selected 11 metrics from Epic Signal, a functionality of the Epic electronic health record (EHR). Metrics measuring time spent in the EHR outside working hours were used as a correlate for burden. We performed an analysis of these metrics among active physicians at our institution across three time periods—prepandemic and telehealth implementation (August 2019), postimplementation of telehealth (May 2020), and follow-up (July 2020)—and correlated them with physician characteristics.Results Analysis of 495 physicians showed that after the start of the pandemic, physicians overall had fewer appointments per day, higher same day visit closure rates, and spent less time writing notes in the EHR outside 7 a.m. to 7 p.m. on patient scheduled days. Across all three time periods, male physicians had better EHR-defined “efficiency” measures and spent less time in the EHR outside working hours. Years since graduation only had modest associations with higher same day visit closure rates and appointments per day in May 2020. Specialty category was significantly associated with appointments per day and same day closure visit rates and also was a significant factor in the observed changes seen across the three time periods.Conclusion Utilizing EHR-generated reports may provide a scalable and nonintrusive way to monitor trends in physician usage and experience to help guide health systems in increasing productivity and reducing burnout.
Keywords: electronic health record; telemedicine; COVID-19 pandemic; burden